2012
DOI: 10.2306/scienceasia1513-1874.2012.38.212
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of essential oils from Citrus hystrix (makrut lime) against respiratory tract pathogens

Abstract: Many essential oils have antibacterial activity with a potential use in medicine. Citrus hystrix DC, or makrut lime, contains two essential oils, makrut leaf oil and makrut (fruit peel) oil, of which we determined the inhibitory effect against respiratory pathogens and evaluated their active components. Gas chromatography-mass spectrometry was used to analyse the chemical composition of the essential oils. The antibacterial activities were tested by disc-diffusion and broth microdilution methods against 411 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 16 publications
1
47
0
1
Order By: Relevance
“…The strong antibacterial activity of S. khuzistanica Jamzad essential oil is most probably related to its carvacrol content. Meanwhile limonene, the other major component of our S. khuzistanica EO (1.2%), has been reported to have weak or no antibacterial activity against bacterial pathogens (31). In conclusion, carvacrol rich essential oil of S. khuzistanica Jamzad showed the strong antibacterial activity against MDR clinical isolates of A. baumannii which can be used for treatment of infections in order to eradicate these pathogens.…”
Section: Discussionmentioning
confidence: 74%
“…The strong antibacterial activity of S. khuzistanica Jamzad essential oil is most probably related to its carvacrol content. Meanwhile limonene, the other major component of our S. khuzistanica EO (1.2%), has been reported to have weak or no antibacterial activity against bacterial pathogens (31). In conclusion, carvacrol rich essential oil of S. khuzistanica Jamzad showed the strong antibacterial activity against MDR clinical isolates of A. baumannii which can be used for treatment of infections in order to eradicate these pathogens.…”
Section: Discussionmentioning
confidence: 74%
“…Soap pod extracts has been demonstrated to have in vitro antioxidant and anti-tyrosinase activities [9]. Kaffir lime possesses antioxidant, antimicrobial, antibacterial properties and the major compounds are sabinene, β-pinene, limonene, α-pinene, camphene, myrcene, terpinen-4-ol, α-terpineol, linalool, terpinolene and citronellal [10][11][12]. The main compounds in the essential oil of lemongrass are the monoterpene citral, a mixtures of the stereisomers geranial , neral and β-myrcene and antioxidant properties has also been reported [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Preclinical studies have shown that the phytochemicals compound of kaffir lime leaf (KLL) and fruit have antioxidant activity, 2 free radical scavenging ability, 2 anti-inflammatory activity, 3 antibacterial activity, 4 antifungal activity, [1][2][3][4][5] and anticarcinogenic activity. 6 Phytochemical studies have shown that citronellal is the main compound found in KLL.…”
Section: Introductionmentioning
confidence: 99%